THE CORRELATION BETWEEN LANGUAGE LEARNING STRATEGIES AND READING COMPREHENSION ACHIEVEMENTS OF THE ELEVENTH GRADE STUDENTS OF SMA N 5 PALEMBANG - Dian Puspita (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
The objectives of this study were to find out (1) whether or not there is a significant correlation between language learning strategies and reading comprehension achievements of the eleventh grade students, (2) whether or not there is a contribution from language learning strategies to reading comprehension achievements of the eleventh grade students. For the data collection, the strategy inventory language learning questionnaire and reading test were distributed to the 91 eleventh grade students of SMA N 5 Palembang. The result showed that (1) there was significant correlation between language learning strategies and reading achievement R 0.447. Categorically, from the six aspects of language learning strategies; memory, cognitive, compensation, affective and social have very weak correlation coefficient to the reading comprehension achievement. While metacognitive has fair correlation coefficient. But, there is significant correlation between all LLS’ aspects and reading comprehension achievement, (2) language learning strategies contributed 20.0% to reading comprehension achievement, especially metacognitive contribute the most.